Respuesta :

[tex] \cfrac{10x^6y^{12}}{-5x^{-2}y^{-6}} =-2x^{6-(-2)}y^{12-(-6)}=-2x^{6+2}y^{12+6}=-2x^8y^{18}[/tex]

Answer: B)-2x^8y^18

Answer: Option 'B' is correct.

Step-by-step explanation:

Since we have given that

[tex]\frac{10x^6y^{12}}{-5x^-2y^-6}[/tex]

We will use two rules :

[tex]a^m\times a^n=a^{m+n}\\\\and,\\\\a^m\div a^n=a^{m-n}[/tex]

So, it will become,

[tex]\frac{10x^6y^{12}}{-5x^{-2}y^{-6}}\\\\\frac{10}{-5}\times \frac{x^6}{x^{-2}}\times \frac{y^{12}}{y^{-6}}\\\\=-2\times x^{6-(-2)}\times y^{12-(-6)}\\\\=-2x^{6+2}\times y^{12+6}\\\\=-2x^{8}y^{18}[/tex]

Hence, Option 'B' is correct.